International Political Communication in The Context of Digitalization of World Development - V. K. Belozerov (Контуры глобальных трансформаций: политика, экономика, право, 2020)
The article is dedicated to exploring the phenomenon of international political communication, changing in the context of world development digitalization. The logic of comprehension and sequence of material presentation stem from a number of circumstances. Firstly, the modern socio- political practice of responding to digitalization is characterized by fragmentation, discreteness and incompleteness. Nevertheless, digitalization is a real phenomenon that has a political dimension, and its manifestations, consequences and exposure perspectives need scientific understanding. Furthermore, the very international political communication remains understudied. The research on communication processes is focused mainly on the domestic sphere. Consequently, the content and direction of changes in the sphere of international political communication under the influence of digitalization are not fully evaluated by the scientific community.The methodological basis of the research is the theory of political communication and realism. The disclosure of the stated topic required the use of structural and functional analysis, document analysis, comparative analysis, and performance analysis. The author derives the definition of international political communication. Based on the study of specialized literature and available examples from practice, problem clusters of international political communication are being identified and characterized, some measures of response to digitalization are being proposed. In order to assess and understand the prospects for responding to the digitalization of international political communication, attention is paid to the study and comparison of the doctrinal documents of Russia, the USA, Germany and Austria. It is substantiated that changes in the practice of international political communication in the context of digitalization will increase.